Investigating N-Alkane Distribution in the Soils of the Basrah’s Oilfield: Sources and Environmental Impact - Resen, Majdalena A.; Abdulhassan, Hamza K.; Al-Saad, Hamid T. (Mesopotamian Journal of Marine Sciences, 2024)
Soil samples were collected at a depth of 0 to 20 cm from 11 oil fields in the Basrah governorate (Seba, Safwan, Majnoon, Ratawi, Bergezia, West Qurna2, West Qurna1, Shuaaba, South and North Rumaila, and Al Zubair). The analysis of every hydrocarbon component was done using gas chromatography and a flame ionization detector. Total n-alkanes have the highest mean concentrations in soil (341.666µg/g dry weight) at Station 7, and the lowest mean concentrations (178.874µg/g dry weight) at Station 4. The CPI readings range from 0.251 in the spring at Station 8 to 1.880 in the summer at Station 5. When the CPI value is more than one, it suggests that the n-alkanes originated biogenically from bacteria, algae, and the wax found on the leaves of vascular higher plants. The C17/Pristane and C18/Phytane Ratios, which show the source of alkanes in soil, indicated that the petroleum had weathered and become older in the soil, whereas the majority of soil samples included isoprenoids, such as phytane and pristane. There were also cases of Unresolved Complex Mixture (UCM). The findings showed that the aliphatic hydrocarbons came from both biogenic and anthropogenic sources. N-alkane distribution is bimodal: odd carbon numbers (C21, C22, C23, C24, and C25) predominate in the Low Molecular Weight (C13-C25) and indicate bacterial activity, while odd carbon numbers (C29, C30, C31, and C32) predominate in the High Molecular Weight (C26-C36), suggesting a source of higher plant wax. Both biogenic and manmade factors contributed to the majority of the oil field.